A comparative study of Cn/Sn/Cu and Ni/Sn/Ni solder joints for low temperature stable transient liquid phase bonding. (December 2015) - Chu, Kunmo; Sohn, Yoonchul; Moon, Changyoul
Graphical abstract: Abstract: Two sandwich structured solder systems (Cu/Sn/Cu and Ni/Sn/Ni) were investigated in terms of interfacial reaction and mechanical reliability for low temperature wafer bonding. The relationship between chemical reaction and mechanical reliability of the solder joints was investigated by varying thickness ratio of Cu/Sn (Ni/Sn). The Cu/Sn/Cu joint was proved to be stronger, revealing very smooth fractured surface through Cu6 Sn5 grains (intragranular fracture). Meanwhile, the Ni/Sn/Ni joint showed rough fractured surface through Ni3 Sn4 grain boundaries and Ni3 Sn4 /Ni3 Sn2 interphase boundaries (intergranular fracture).